'An "authentic" performance?: the cultural politics of "folk" in Bengal and Bangladesh'. Issue 3 (3rd July 2019) - Basu, Priyanka
ABSTRACT: Kabigāna is a verse-duelling/song-theatre genre practiced in West Bengal (India) and Bangladesh. Often deemed as obsolete and extinct – following from urban perceptions and the canons of literary history – the genre is found to grapple with the questions of 'authenticity' across its multiple spaces of performances- rural rituals, urban fairs/festivals, cinematic representations as well as packages for television and the new media. This article introduces the performance genre of Kabigāna by trying to understand its format and content as an entity that is separate from the umbrella term of 'folk performances'. It contains two case studies of contemporary Kabigāna performances in rural West Bengal and Bangladesh to understand how performers themselves negotiate the complex idea of 'authenticity'. Finally, it tries to address some key issues of the cultural politics of performances by bringing in a number of claimants for the genre and exploring if any of these claimants 'own' it ultimately. Following an ethnographic method of enquiry and analyses of documented performances, this article tries to bring out the nuances of the performance genre that has mostly been lost in literary canons and official archives. In this sense, the findings of the fieldwork presented in this article is an approach towards re-reading the archival texts, performances and institutional practices and politics in relation to each other.